The Mindset Change of a Saving Paradigm in to an Investment Paradigm: A Managing Finance for Indonesian Students in the Philippines - Permatasari, Intan Kurnia; Permatasari, Ika; Laksono, Bayu Rama; Putikadea, Insyirah (PT Inovasi Pratama Internasional, 2025)
The purpose of this community service activity is to introduce the latest investment instrument products to the public, especially Indonesian students in the Philippines, on the importance of financial literacy knowledge in improving financial management skills through investment instruments. This is important to do considering that investment is a provision for students in terms of financial management, so that during the study abroad period students can manage finances wisely and have a long-term thinking orientation. If supported by strong financial planning and adequate management skills, then development constraints for the long term in terms of finance will be optimally mitigated. The method used in achieving this goal is training on the introduction of investment instruments and how to choose investment instruments, how to transact in investment, how to determine which investments are good and bad, investment strategies, and maintaining the psychological stability of an individual investor. The evaluation results showed that 90% of the training participants agreed that during the training the students gained new insights on how to invest and helped the students understand the importance of managing finances well. This community service activity received a positive response and motivated participants to be more actively involved in increasing their interest in investment. A total of 98% of participants were interested in investing. Of the 98% who were interested in investing, 40% chose mutual funds as their investment instrument, 19% chose stocks, 17% chose bonds, 5% chose property, 2% chose crypto, and the remaining 17% had yet to decide which investment instrument to choose. The recommendation given to students to advance their understanding of investment is that students are expected to set aside 10-20% of their pocket money every month for low to medium risk investments, such as mutual funds, deposits, or precious metals.